Ohmic Heating Effect on Magneto Hydrodynamic Marangoni Mixed Convection Boundary Layer Nanofluid Flow - Srinivasu, M.; R.V.S.R.K.Sastry, Devulapalli; V.S.R.Deekshitulu, G. (International Journal of Engineering and Technology, 2018)
In surface driven flows, dissipative layers which occur along the surface of two immiscible fluids are known as marangoni boundary layers. Mixed connection takes place when buoyancy forces act beside marangoni effect. Consider a nanofluid flow along a flat surface experiencing marangoni convection with ohmic dissipation and magnetic field. Copper and Alumina are the nanoparticles with water as base fluid. The similarity equations are solved numerically by BVP solver â€˜bcp4câ€. The flow characteristics are analyzed graphically and discussed.Â Â